Cohort profile: the Australian Longitudinal Study of Adults with Autism (ALSAA). Issue 12 (4th December 2019) - Arnold, Samuel; Foley, Kitty-Rose; Hwang, Ye In (Jane); Richdale, Amanda L; Uljarevic, Mirko; Lawson, Lauren P; Cai, Ru Ying; Falkmer, Torbjorn; Falkmer, Marita; Lennox, Nick G; Urbanowicz, Anna; Trollor, Julian
Abstract : ​Purpose: There is a significant knowledge gap regarding the lives of adults on the autism spectrum. Some literature suggests significant health and mental health inequalities for autistic adults, yet there is a lack of comprehensive longitudinal studies exploring risk factors. Further, most research does not include the perspective of autistic adults in its conduct or design. Here, we describe the baseline characteristics and inclusive research approach of a nationwide longitudinal study. ​Participants: The Autism Cooperative Research Centre for Living with Autism's Australian Longitudinal Study of Adults with Autism (ALSAA) is a questionnaire-based longitudinal study of autistic adults (25+ years old) with follow-up at 2-year intervals. Autistic advisors were involved in each stage of research apart from data analysis. Three questionnaires were developed: self-report, informant report (ie, proxy report) and carers (ie, carer experiences and characteristics). ​Findings to date: An inclusive research protocol was developed and agreed with autistic advisors. Baseline data were collected from 295 autistic adults (M=41.8 years, SD=12.0) including 42 informant responses, 146 comparison participants and 102 carers. The majority of autistic participants (90%) had been diagnosed in adulthood (M=35.3 years, SD=15.1). When compared with controls, autistic adults scored higher on self-report measures of current depression and anxiety. Participant comments informed ongoing data gathering. Participants commented on questionnaire length, difficulty with literal interpretation of forced response items and expressed gratitude for research in this area. ​Future plans: A large comprehensive dataset relating to autistic adults and their carers has been gathered, creating a good platform for longitudinal follow-up repeat surveys and collaborative research. Several outputs are in development, with focus on health service barriers and usage, caregivers, impact of diagnosis in adulthood, further scale validations, longitudinal analyses of loneliness, suicidal ideation, mental illness risk factors and other areas. Baseline data confirm poorer mental health of autistic adults. The ALSAA demonstrates a working approach to inclusive research.